2010
DOI: 10.1056/nejmoa1002315
|View full text |Cite
|
Sign up to set email alerts
|

Dasatinib versus Imatinib in Newly Diagnosed Chronic-Phase Chronic Myeloid Leukemia

Abstract: Dasatinib, administered once daily, as compared with imatinib, administered once daily, induced significantly higher and faster rates of complete cytogenetic response and major molecular response. Since achieving complete cytogenetic response within 12 months has been associated with better long-term, progression-free survival, dasatinib may improve the long-term outcomes among patients with newly diagnosed chronic-phase CML. (ClinicalTrials.gov number, NCT00481247.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
1,277
6
25

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,414 publications
(1,358 citation statements)
references
References 29 publications
34
1,277
6
25
Order By: Relevance
“…QTc prolongation was frequent (>5% of patients experiencing CTCAE scale grade I QTc prolongation) in patients treated with dasatinib, vandetanib, sorafenib, or sunitinib. Dasatinib is used to treat hematological malignancies and has been associated with QTc prolongation in 8% of treated patients (range, 1%–70%), but QTc >500 ms was seen only in <1% 13, 18, 20, 21, 22, 25, 32, 40, 42, 75…”
Section: Resultsmentioning
confidence: 99%
“…QTc prolongation was frequent (>5% of patients experiencing CTCAE scale grade I QTc prolongation) in patients treated with dasatinib, vandetanib, sorafenib, or sunitinib. Dasatinib is used to treat hematological malignancies and has been associated with QTc prolongation in 8% of treated patients (range, 1%–70%), but QTc >500 ms was seen only in <1% 13, 18, 20, 21, 22, 25, 32, 40, 42, 75…”
Section: Resultsmentioning
confidence: 99%
“…14 In the DASISION trial, 46% of patients treated with dasatinib 100 mg once daily achieved MMR by 12 months, whereas only 28% achieved MMR on imatinib (Po0.0001). 10 By 24 months, CMR 4.5 was achieved in 17% and 8% of patients treated with dasatinib or imatinib (P ¼ 0.002 vs imatinib). 15 Similar response to dasatinib has also been demonstrated in the phase 2 MDACC trial, with 6% of patients achieving CMR 4.5 by 18 months, 7 and in the Southwestern Oncology Group trial, with 27% of patients achieving CMR 4 at 12 months in evaluable patients (P ¼ 0.31 vs imatinib).…”
Section: Second-generation Tki's In the Front-line Setting: Molecularmentioning
confidence: 95%
“…5,6 Similarly, the Southwestern Oncology Group and MDACC trials of dasatinib in patients with newly diagnosed CML-CP demonstrated CCyR rates of 82-98% by 12 months. 7,8 The pivotal phase 3 nilotinib (ENESTnd) 9 and dasatinib (DASISION) 10 trials showed rates of CCyR of 80% and 83% for nilotinib and dasatinib, respectively, by 12 months (rates of CCyR in the phase 3 studies are likely lower than those in phase 2 studies due to the 1 application of the intention-to-treat principle and that patients with missing or non-evaluable samples were considered as nonresponders). In the ENESTnd trial, 55% of patients treated with nilotinib 300 mg twice daily achieved MMR by 12 months, whereas only 27% achieved MMR on imatinib (Po0.0001).…”
Section: Second-generation Tki's In the Front-line Setting: Molecularmentioning
confidence: 99%
“…7 When dasatinib was tested, first-line treatment compared with imatinib, the responses were faster and superior, and the molecular response was also deeper. 19,20 The follow-up of the patients treated first line with dasatinib is still short, less than 3 years. The major side effects of dasatinib are leucopenia, thrombocytopenia, pleural effusion and pulmonary complications.…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 99%